Highly sustainable cascade pretreatment of low-pressure steam heating and organic acid on pineapple waste biomass for efficient delignification - Norhafiza, Nordin; Rosli, Md Illias; Nor Hasmaliana, Abdul Manas; Aizi Nor Mazila, Ramli; Selvasembian, Rangabhashiyam; Nur Izyan, Wan Azelee; Rajagopal, Rajinikanth; Thirupathi, Anand; Chang, Soon Woong; Ravindran, Balsubramani (Elsevier Ltd, 2022)
Cascade pretreatment of low-pressure steam heating (LPSH) and maleic acid (MA) on pineapple waste (PW) biomass aims to improve delignification, increase enzyme accessibility to carbohydrate in the feedstock while reducing inhibitor by-products. The best conditions for LPSH pretreatment were determined using one-factor-at-a-time (OFAT) while the conditions of MA pretreatment (temperature, acid concentration and time) were optimized by Box-Behnken design. A total of 68% (w/w) delignification with 79.5% (w/w) hemicellulose removal were achieved while 77.6% (w/w) cellulose was retained in the solid residue after the cascade pretreatment. No 5-hydroxylmethyl furfural (5-HMF) and acceptable furfural (1.8 g/L) were detected in the hydrolysate by high performance liquid chromatography analysis, with negligible amount of phenolic compounds (0.01 g/L). Compared to the pretreatment with combined LPSH and conventional sulphuric acid pretreatment (H2SO4), the pretreated PW produced 3.6 g/L of furfural and 0.4 g/L of HMF at similar optimized conditions. The pretreated PW were further characterized by scanning electron microscopy and Fourier transform infrared spectroscopy to analyze structural morphology and functional group changes. The pooled solid and liquid hydrolysate fractions generated from the LPSH and MA cascade pretreatment and subsequent enzyme hydrolysis has successfully generated 356.32 mg/g glucose and 156.91 mg/g xylose. The optimized cascade pretreatments provide up to 54.79% of glucose yield and 69.23% of xylose yield. Furthermore, 67.87% reduction of lignin content from the cascade pretreatment can substantially enhance the glucose yield up to 95.76% and xylose yield up to 99.07% during enzymatic hydrolysis using the mixture of cellulase and hemicellulase.